Faktor-Faktor yang Mempengaruhi Stres Akademik - Nur Mawakhira Yusuf; Jannatul Ma’wa Yusuf (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2020)
Academic stress is an individual condition that arises because of the amount of pressure or academic demands that exceed their capacity so that individuals feel burdened. The purpose of this study is to identify the factors that influence academic stress. Literature searches were carried out in the electronic database Researchgate, Scopus, Springer, and Google Schoolar using the keywords